CUSTOMER SERVICE CHAT APPLICATION DESIGN RADEN INTEN II AIRPORT, LAMPUNG - Mezan El-Khaeri Kesuma; Indra Gunawan; M. Alif Ridho Setiawan (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2025)
This study aims to design a web-based customer service application with live chat and chatbot features that implement Retrieval-Augmented Generation (RAG) technology at Raden Inten II Airport, Lampung. The main problems encountered are the slow response of conventional services and limited access to information by users located far from the airport. The system development uses the Waterfall model which includes requirements analysis, system design, implementation, testing, and maintenance. The main features in the application include user authentication, live chat, RAG chatbot, and data management through the admin dashboard. System testing was conducted using the black-box method, indicating that all features function according to specifications. The results of the study indicate that this system can significantly improve the efficiency and quality of customer service. For further development, it is recommended to use WebSocket to improve real-time communication performance. Index Terms— Customer Service; Live Chat; Chatbot; RAG; Web-based Application.